Hot and cold - Davies, Kay and Wendy Oldfield (Wayland, Hove, 1991)
"Hot and Cold" by Kay Davies and Wendy Oldfield, published in 1991, is part of the "Starting Science" series. This 32-page book introduces young readers to the concepts of temperature and its effects on materials. Through full-page photographs and engaging activities, it explores how objects change when heated or cooled, providing a hands-on approach to understanding thermal properties. The book is designed to make science accessible and enjoyable for children, aligning with early educational standards.